Studi Pemanfaatan Tumbuhan Obat Antidiare oleh Masyarakat di Etnis Sumatera Utara - Helen Anjelina Simanjuntak (Herbal Medicine Journal, 2021)
Diarrhea is one of the digestive disorders characterized by loose, liquid and watery bowel movements (defecation) with a frequency of three times a day accompanied by cramps in the stomach. This disorder is caused by a bacterial infection and an imbalance between the mechanisms of absorption and secretion of water and electrolytes in the intestinal tract and is accompanied by hypermobility. In Indonesia, diarrheal disease is the second cause of death for children under the age of 5 years. Indonesia is a country that has the 2nd highest biodiversity with a diversity of medicinal plants, especially in the treatment of diarrheal diseases. The research method is carried out using a literature review with online media based on the Web, Scopus, PubMed, Science Direct, ResearchGate, Google Scholar used for publication. The results show that there are medicinal plants used as diarrhea medicine (antidiarrhea) consisting of 14 orders, 16 families, and 19 species, namely Acorus americanus (Far.) Raf., Ageratum conyzoides L., Blumea balsamifera (L).DC., Bischofia javanica Bl., Dioscorea alata L., Allium cepa L., Psidium guajava L., Cymbopogon citratus (DC.) Stapf., Kalanchoe pinnata (Lam.) Pers., Uncaria gambir (Hunter) Roxb., Lansium domesticum Correa., Nephelium lappaceum L., Strobilanthes crispus Blume., Solanum nigrum L., Solanum torvum Sw., Artocarpus heterophyllus Lam., Carica papaya L., Curcuma longa L., and Curcuma xanthorrhiza Roxb.